Kooiichthys jono n. gen. n. sp., a primitive catfish (Teleostei, Siluriformes) from the marine Miocene of southern South America. (24th March 2016) - Azpelicueta, María de las Mercedes; Cione, Alberto Luis; Cozzuol, Mario Alberto; Mirande, Juan Marcos
Abstract: A specimen of a remarkable new catfish genus and species was collected in middle/late Miocene marine beds of the Puerto Madryn Formation at the base of the marine cliff of the sea lion colony area near Puerto Pirámide, southern coast of Península Valdés, northeastern Patagonia, Argentina. Siluriforms (catfishes) constitute a most important monophyletic ostariophysan group of mainly freshwater fishes that occurs in almost all continents but it is especially diverse in South America. Catfishes are presently distributed in tropical to temperate areas and a small number of species are marine or amphibiotic. The new catfish shows many primitive features for catfishes in the maxilla, autopalatine, hyal elements, and Weberian apparatus. The genus is clearly distinguished by four autapomorphies: sand clock–shaped autopalatine, posterior limb of autopalatine widening strongly, post-articular arm of autopalatine longer, and a metapterygoid longer than broad. One tree was obtained both under equal and implied weighting with the following topology: a basal polytomy in the Siluriformes formed by Diplomystidae, Bachmanniidae, Kooiichthys and the Siluroidei. The new species appears to have been a marine or amphibiotic taxon: it was collected in beds considered to represent the Maximum Flooding Horizon of the transgression that deposited the Puerto Madryn Formation. The coast at this moment was at approximately 90 km to the west. According to faunistic evidence, the sea was warm temperate.